ANALISIS PENGARUH KURS, INFLASI DAN HARGA BATUBARA ACUAN TERHADAP EKSPOR BATUBARA INDONESIA KE CHINA - Barasyid, Alfariz Iqbal; Setiawati, Ririt Iriani Sri (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The purpose of this study was to determine the effect of the exchange rate, inflationand reference coal prices on Indonesian coal exports to China. In this study theauthors used quantitative data obtained from sources related to this study. Thevariables used by the author are the Exchange Rate (X1), Chinese Inflation (X2),Reference Coal Prices (X3) and Indonesian Coal Exports to China (Y). The type ofdata used in this study is time series data for 2009-2021 and the authors use themultiple linear regression analysis method, the classical assumption test and the Ttest or statistics. the exchange rate variable has a significant effect on Indonesiancoal exports to China, while the inflation variable has no significant effect onIndonesian coal exports to China and finally the reference coal price variable hasa significant effect on Indonesian coal exports to China. The results of the researchconducted by the author can be concluded that all independent variables, namelyexchange rate variables (X1), inflation (X2) and reference coal prices (X3) resultin an influence on the dependent variable, namely Indonesian coal exports to China(Y).Keywords: Exchange Rates, Exports, Indonesian Coal Exports to China, Inflation,Reference Coal Prices